2015
DOI: 10.15537/smj.2015.2.9603
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the American Diabetes Association standards of care among patients with type 2 diabetes in primary care in Saudi Arabia

Abstract: Objectives:To assess adherence to 11 American Diabetes Association (ADA) standards of diabetic care.Methods:We conducted this one-year historical prospective study between October 2010 and September 2011 on 450 adult type 2 diabetes patients in a primary care center in Saudi Arabia. We used the definitions of the 2010 ADA standards of diabetic care processes and targets.Results:Four-hundred and fifty medical files were valid. The adherence to ADA process standards of measurement of glycated hemoglobin (HbA1c) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 27 publications
2
28
3
Order By: Relevance
“…We obtained the cut-point value of 4.39 mmol/L. Following the ADA criteria, some studies showed that only 58.5 % of the patients reached the target LDLc value during treatment, while 7.2% achieved the target values for both LDLc and HbA1c simultaneously 22 . In favor of and in addition to previously stated, the treatment of dyslipidemia in the DM patients should be commenced earlier, from the very onset of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained the cut-point value of 4.39 mmol/L. Following the ADA criteria, some studies showed that only 58.5 % of the patients reached the target LDLc value during treatment, while 7.2% achieved the target values for both LDLc and HbA1c simultaneously 22 . In favor of and in addition to previously stated, the treatment of dyslipidemia in the DM patients should be commenced earlier, from the very onset of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, frequent FP attendance has no positive impact on guideline adherence. Frequent patient attendance has been found positively associated with better guideline adherence by the studies carried out in Australia [32], Saudi Arabia [33]. The relationship between the higher performance and frequent attendance raises doubts about the efficiency of a diabetes patient management pattern.…”
Section: Discussionmentioning
confidence: 99%
“…10 Two studies reported that inadequate control of blood glucose levels are due to minimal adherence of prescribers to standard guidelines. 11,12 However, many studies revealed that after publishing AACE/ACE guidelines there was significant difference in drug therapy based on A1c levels prescribed by physicians in United States of america. 13 Another study published that there was optimal adherence to guidelines in Sweden in home health care settings than residents at nursing homes.…”
Section: Discussionmentioning
confidence: 99%